The effect of preloading on the mechanical properties of polymeric foams - Ozkul, M. H.; Mark, J. E. (Wiley, 1994)
AbstractThe polymeric foams investigated with regard to their mechanical properties were the rigid foams polystyrene, polyurethane, and phenolic, and the semirigid foam polyethylene. Preloading of the rigid foams was found to decrease the modulus by an amount that increased as the extent of preloading increased, and to decrease both the modulus and collapse stress in the case of the semirigid ones. The shape of the stress‐strain curves of the foams was also significantly changed by the preloading, and a reduction in cushioning properties in static compression was observed.